Hubungan Aktivitas Fisik dan Pola Makan terhadap Status Indeks Masa Tubuh Normal - Aulia Rizky Ramadhania; Azwaj Nailla Hasna; Rieke Kartika Winata; Heri Ridwan; Popi Sopiah (Yayasan Literasi Sains Indonesia, 2024)
Body Mass Index (BMI) is a simple method used to assess the nutritional status of an individual. BMI is related to risk factors for obesity and its complications. Knowledge is needed regarding matters related to BMI in order to be able to control it and keep it in a normal or ideal state. This research aims to explain the relationship between physical activity and Body Mass Index (BMI) as well as good eating patterns to control BMI to remain normal. The research was conducted using the literature review method. Literature reviews were carried out on research articles, books and government documents. The results found that physical activity was related to BMI in terms of energy burning and fat reserves in the body. Insufficient physical activity will lead to a tendency towards high BMI values. Vice versa, high physical activity tends to set lower (normal) BMI values. Apart from managing physical activity, in order to get an ideal BMI, you need to regulate your diet well, namely by paying attention to the type, amount and schedule of food consumption.